Carbapenemases‐producing Klebsiella pneumoniae in hospitals of two regions of Southern Italy. Issue 5 (15th March 2017) - Calia, Carla; Pazzani, Carlo; Oliva, Marta; Scrascia, Maria; Lovreglio, Piero; Capolongo, Carmen; Dionisi, Anna Maria; Chiarelli, Adriana; Monno, Rosa
Abstract : Carbapenem‐resistant Klebsiella pneumoniae infections are reported with increasing frequency elsewhere in the world, representing a worrying phenomenon for global health. In Italy, there are hotspot data on the diffusion and type of carbapenemase‐producing Enterobacteriaceae and K. pneumoniae in particular, with very few data coming from Apulia and Basilicata, two regions of Southern Italy. This study was aimed at characterizing by phenotypic and genotypic methods carbapenem‐resistant K. pneumoniae isolated from several Hospitals of Apulia and Basilicata, Southern Italy. Antibiotic susceptibility was also evaluated. The relatedness of carbapenemase‐producing K. pneumoniae strains was established by pulsed‐field gel electrophoresis (PFGE). Among the 150  K. pneumoniae carbapenemase producers, KPC‐3 genotype was the most predominant (95%), followed by VIM‐1 (5%). No other genotypes were found and no co‐presence of two carbapenemase genes was found. A full concordance between results obtained by both the phenotypic and the genotypic tests was observed. All strains were resistant to β‐lactam antibiotics including carbapenems, and among antibiotics tested, only tetracycline and gentamycin showed low percentage of resistance (18% and 15%, respectively). Resistance to colistin was detected in 17.3% of strains studied. The analysis of PFGE profiles of the carbapenemases‐positive strains shows that one group (B) of the five (A to E) main groups identified was the most prevalent and detected in almost all the hospitals considered, while the other groups were randomly distributed. Three different sequence types (ST 307, ST 258, and ST 512) were detected with the majority of isolates belonging to the ST 512. Our results demonstrated the wide diffusion of K. pneumoniae KPC‐3 in the area considered, the good concordance between phenotypic and genotypic tests. Gentamicin and colistin had a good activity against these strains.